FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK BIDAN DALAM PELAKSANAAN DETEKSI DINI PRE EKLAMPSI PADA IBU HAMIL DI KABUPATEN BREBES - Tatirah tatirah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Case Maternal deaths in Brebes Regency in 2021 were 105 cases of which 9 cases of bleeding, 28 cases of preeclampsia, 1 case of infection in pregnancy, 4 cases of heart disease and others 63 cases were caused by covid 19. 192 cases of multiple pregnancy (gemelli) and 1,614 cases of anemia in pregnant women. Preeclampsia is one of the cases of pregnancy disorders that can be a cause of maternal death. This disorder occurs during pregnancy, childbirth and the puerperium which will have an impact on the mother and baby. Preeclampsia is more common in women who have had twins because a woman with multiple pregnancies has a larger blood volume and an extra burden on the cardiovascular system that can predispose to induced hypertension and develop preeclampsia and eclampsia.This study aims to analyze the factors related to the practice of midwives in the implementation of early detection preeclampsia in pregnant women in Brebes Regency. This research is a survey research with cross sectional design. The research population is all midwives who work in the Brebes Regency area. Sampling technique with clustered random sampling at the sub-district level with the sub-district as a cluster, and 122 subjects, respondents were interviewed using a structured questionnaire. Data were analyzed by chi square and multiple logistic regression. The independent variables consisted of age, education, years of service, knowledge of the midwife about preeclampsia, attitudes, motivation, compensation system, supervision by the Head of Health Care Unit/IBI and medical equipment facilities. The dependent variable is the practice of midwives in the implementation of early detection of preeclampsia.The results showed that there was a relationship between knowledge (p = 0.030), attitude (p = 0.0001), motivation (p = 0.0001), compensation system (p = 0.019), and supervision by the Head of Health/IBI (p =0.012) with the practice of midwives in the implementation of early detection of preeclampsia. Age, education, years of service and medical device facilities are not related to the practice of midwives in the implementation of early detection of preeclampsia.The results of the multivariate analysis showed that the factors that jointly influenced the practice of midwives in the implementation of early detection of preeclampsia in pregnant women were attitude with (p = 0.027), motivation (p = 0.0001), compensation system (p = 0.002), and supervision by case of kesga/IBI (p = 0.047).The most dominant influencing factor was the midwife's motivation (OR = 8,292). Recommended to the health office to increase the motivation of midwives by conducting regular supervision of the puskesmas or BPS and providing training to midwives, improving the attitude of midwives to be more supportive of the practice of midwives in the implementation of early detection of preeclampsia.